Examining Aboriginal Employment: 2007–2014 - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2015)
The employment, unemployment and participation rates are examined for Aboriginals living off-reserve in Canada from 2007 to 2014 as well as for non-Aboriginals for those 15 years and older. Employment is analyzed by educational level, gender and age, province and by industrial sector. The rates of employment and unemployment for Aboriginals have continued to improve in 2014, lessening the differences with non-Aboriginals. These improvements occurred in each age category for both men and women, except for the unemployment rate of Aboriginal women in the 25 to 54 year old group. The Metis employment, participation and unemployment rates have been more favourable than the First Nations for each year from 2007 to 2014.The level of education obtained continued to show a strong positive relationship with the rate of employment for Aboriginals and non-Aboriginals. When employment rates are examined by educational level, there is very little difference between Aboriginals and non-Aboriginals. However educational level does not explain the differences in unemployment rates. The highest rate of employment for Aboriginals and non-Aboriginals in 2014 continued to be in Alberta. Employment continued to increase in the services-producing sector, but decreased in the goods-producing sector for Aboriginals and non-Aboriginals in 2014.